Halal Milkfish Processing Business Development Strategy by the Junok Sreseh Sampang Village Community Association Group - Ulfiyah; Mashudi; Dahruji (Penerbit Hellow Pustaka, 2025)
Junok Village, Sreseh District, Sampang Regency, has a favorite milkfish that is favored by consumers in the surrounding districts and other consumers. Based on the availability of abundant milkfish resources, the milkfish processing business in Junok Village has not been fully developed. Therefore, research activities were conducted. This study aims to determine the strategy for developing halal milkfish processing businesses by the Junok Sreseh Sampang Village Community Association. This study uses a qualitative descriptive research method and uses a field study approach. Data collection techniques were obtained through interview and observation methods. By using data collection, data reduction, data presentation, and conclusions in analyzing data. The results of the study indicate that the halal business development strategy in Junok Village has not been fully implemented, as seen from several important aspects that still require attention. Although there is awareness of the importance of halal products, many producers in Junok Village do not have official halal certification, which can increase consumer confidence. Therefore, training is needed to improve understanding of halal, as well as collaboration with related institutions to help producers obtain halal certification.